2013
DOI: 10.1186/1471-2318-13-85
|View full text |Cite
|
Sign up to set email alerts
|

What determines the self-rated health of older individuals with stroke compared to other older individuals? A cross-sectional analysis of the Medical Research Council Cognitive Function and Aging Study

Abstract: BackgroundPoor self-rated health has been associated with poorer objective health outcomes across a range of conditions including stroke. Identification of factors associated with poor self-rated health in stroke survivors has received little attention compared to that in other older individuals. This study identifies determinants of self-rated health in older individuals with or without a history of stroke participating in the population-representative MRC Cognitive Function and Aging Study (MRC CFAS).Methods… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
26
0
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(29 citation statements)
references
References 43 publications
2
26
0
1
Order By: Relevance
“…Better self‐rated health predicted a higher amount of PA. Self‐rated health has been consistently identified as a predictor of PA in older adults (Dogra, ). In addition, self‐rated health has been reported to be a significant predictor of health outcomes (Mavaddat, Van der Linde, Savva, Brayne, & Mant, ). PA might play a mediating role between self‐rated health and health outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…Better self‐rated health predicted a higher amount of PA. Self‐rated health has been consistently identified as a predictor of PA in older adults (Dogra, ). In addition, self‐rated health has been reported to be a significant predictor of health outcomes (Mavaddat, Van der Linde, Savva, Brayne, & Mant, ). PA might play a mediating role between self‐rated health and health outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…Pode-se perceber, por exemplo, que sequelas motoras, e principalmente a depressão, são fatores determinantes na postura do usuário em relação à sua própria saúde. 14 Os déficits também se destacam, pois significativo porcentual de usuários declarou apresentar déficits prévios, como sequelas de AVE anteriores ou de outras doenças ou traumas. Esse fato é interessante no momento da avaliação dos novos déficits adquiridos a partir do episódio atual de AVE.…”
Section: Conclusãounclassified
“…Stroke recovery is known to be multidimensional and complex process (Vanhook, 2009) and carries long-term impacts on health. Survivors generally rated their health worse, as compared with the stroke-free general population (Larsen, Johnsen, Andersen, & Hjollund, 2016;Mavaddat et al, 2013). While poor physical health contributed significantly to poor self-rated health (Mavaddat et al, 2013), social factors that encourage activities out of the home seemed to moderate the effects of poor physical health (Larsen et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…SRH correlated well with objective health (Hunt et al, 1980), but has been more strongly associated with physical health than mental health (Smith, Avis, & Assmann, 1999). Studies of older adults have shown that mental, social and physical dimensions contributed to an individual's assessment of their SRH (Mavaddat, Van der Linde, Savva, Brayne, & Mant, 2013), which may involve complex cognitive processes (Jylhä, 2009) that are also influenced by the personal, social and cultural identities of the individual (McMullen & Luborsky, 2006), otherwise known as the environmental and contextual factors that surrounds and shapes the individual. Therefore, SRH may capture elements of health that structured questionnaires may not due to its inclusive nature (Jylhä, 2009).…”
Section: Introductionmentioning
confidence: 99%